1968
DOI: 10.1021/ja01018a038
|View full text |Cite
|
Sign up to set email alerts
|

The hydrolysis of N-substituted acetimidate esters

Abstract: facilitation of hydrolysis attributable to the 6-methyl and 6-chloro groups in this series.Methyl 2-Formyl, 2-Acetyl-, and 2-Benzoylbenzoates. In the three unsubstituted esters, methyl o-formylbenzoate (111)) methyl o-acetylbenzoate (11)) and methyl o-benzoylbenzoate (I), the alkaline hydrolysis may conceivably proceed via two mechanisms: (1) attack of hydroxide ion at the carbonyl function as in the case of the 6-substituted esters, and (2) the normal attack of the hydroxide ion at the carbomethoxy function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

1970
1970
1989
1989

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 0 publications
0
13
0
4
Order By: Relevance
“…A relevant case is the comparative hydrolysis of N-substituted acetimidate esters. 33 During acid hydrolysis, the tetrahedral intermediates from addition of water are similar for the imidate (6) and carbamate cleavage of the C= N bond with ethyl N-phenylacetimidate significantly faster than an N-alkylacetimidate. Kinetic analysis showed that addition of water to the N-protonated acetimidates was the key discriminating factor.…”
Section: Comparison Of N-alkyl and N-aryl Analogsmentioning
confidence: 98%
“…A relevant case is the comparative hydrolysis of N-substituted acetimidate esters. 33 During acid hydrolysis, the tetrahedral intermediates from addition of water are similar for the imidate (6) and carbamate cleavage of the C= N bond with ethyl N-phenylacetimidate significantly faster than an N-alkylacetimidate. Kinetic analysis showed that addition of water to the N-protonated acetimidates was the key discriminating factor.…”
Section: Comparison Of N-alkyl and N-aryl Analogsmentioning
confidence: 98%
“…[I], S . 24 Die Stabilitat von Amidinium-Salzen des Strukturtyps 17a bzw. 16a gegeniiber Hydrolyse ist stark vom pH-Wert der Losung abhangig.…”
Section: )unclassified
“…In den NMR-Spektren sind die Signale dieser Endgruppe nicht auszumachen, und es ist moglich, dass die Konstitution dieser Kopfgruppe nicht einheitlich ist. Nach Literaturdaten [24] konnte die Imidthioester-Gruppe zwar die durch die Bedingungen der Polykondensation (gepufferte wasserige Losung pH &7/0") gegebene Hydrolyse-Gefahr uberstehen, doch besteht letztere vor allem auch wiihrend der Aufarbeitung, da dieselbe saure Phasen durchlauft. Es ist wahrscheinlich, dass die Kopfgruppe zumindest zum Teil als primare Amid-Gruppe vorliegt.…”
Section: Poly(dipeptamidinium)-salze Der (L-alanyl-g1ycin)-reihe Dunclassified
See 2 more Smart Citations